2023
DOI: 10.3390/f14040812
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the International Competitiveness of Forest Products in Top Exporting Countries Using the Deviation Maximization Method with Increasing Uncertainty in Trading

Abstract: Increased uncertainty in the trade environment has become a reality. However, so far, there is no well-established indicator system to quantify the international competitiveness of forest products in the context of increased uncertainty in the trade environment. Based on expanding the concept of international competitiveness, we constructed an evaluation indicator system of international competitiveness including market performance and competitive advantage, which highlighted market stability and market sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…This suggests that a 1% increase in the quality of forest products contributes more to an improvement in international competitiveness than a 1% reduction in the price of their products. In summary, the quality of forest products plays a more obvious role in improving the competitiveness of forest products than does the price, which is consistent with the author's viewpoint in another paper, that is, the current improvement in the international competitiveness of forest products is mainly a result of the improvement in product quality [20].…”
Section: Analysis Of Overall Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This suggests that a 1% increase in the quality of forest products contributes more to an improvement in international competitiveness than a 1% reduction in the price of their products. In summary, the quality of forest products plays a more obvious role in improving the competitiveness of forest products than does the price, which is consistent with the author's viewpoint in another paper, that is, the current improvement in the international competitiveness of forest products is mainly a result of the improvement in product quality [20].…”
Section: Analysis Of Overall Resultssupporting
confidence: 86%
“…Su Haiying et al (2020) found that China's exported forest products are in low-value-added, but its participation in global value chains is gradually increasing [1]. Jiang Bo and Dai Yongwu (2023) analyzed the competitiveness of forest products in major countries and found that improved quality enhances the international competitiveness of major forest product [20]. In addition, factors affecting international competitiveness include the green certification of products, level of technology, and consumer preferences in export markets [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of the availability of inter-country input-output tables, it is natural to use trade data to measure international competitiveness [32]. Noticeably, there are studies using traditional trade statistics to showcase China's competitiveness in some specific products, such as wooden furniture, wood-based panels, and wooden articles [33][34][35]. However, China is also the world's largest importer of log and lumber, and these imported raw materials are major inputs of manufactured wooden products.…”
Section: "Big Yet Not Strong" Is Still the Issue For China's Forestry...mentioning
confidence: 99%